Performance Evaluation Criteria for Hospitals\' Managers: A Qualitative Study - Abbas Pezeshki; Anahita Almasian; Saeid Salehi; Faezeh Zahabi; Mehrdad Jahanfar; Hafez Amraei; Mohammad Keshvari (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Hospitals are the most important element of the health system. Hospitals play a key role in providing health services and have a major impact on the health system's performance. The success of organizations depends on their managers' performance. Organizations with qualified and experienced managers will be more successful in achieving their goals and can reach optimal efficiency. Methods: This is a phenomenological qualitative study in which content analysis was used to achieve study objectives. The study population included the hospitals managers and senior experts of the vice chancellor for treatment of a provincial department of the Ministry of Health and Medical Education in Iran. Participants were selected by purposive and heterogeneous methods and data collection continued until data saturation was achieved. Data were collected by semi-structured face-to-face interviews. Results: From our data, seven main themes were drawn, consisting of monitoring and control, planning, organizing, leadership and motivational factors, management of resources and information, communication and interdepartmental coordination and patient orientation Conclusion: Hospital managers play a key role in improving hospital function. Assessing hospital managers' performance, determining their strengths and weaknesses and taking corrective actions are beneficial to the improvement of hospitals' performance.